Application of AI in Academic Library Services: Prospects and Implications for Quality Service Delivery - Donkor, Antonia Bernadette; Afrane, Daniel Akwasi (IGI Global, 2023)
Academic libraries are mandated to support the information needs of their students, staff, and faculty. In the current technological environment and the influx of artificial intelligence technology into services provision and delivery, this study assessed the knowledge and perception of librarians on the use of AI in library services provision in Ghana. The population for the study consisted of librarians from all 15 public universities in Ghana. Findings from the study revealed that the librarians were knowledgeable of the emergence of AI and sources their information on AI mainly from research articles. It was also revealed that educational level had a significant positive (r= 0.3, p<0.01) relationship with the sources of knowledge on AI tools and applications. There was a positive significant relationship (r= 0.533, p<0.01) between educational level and the frequency of knowledge acquisition on the application of AI in academic library services provision. Academic libraries are encouraged to invest in AI tools and applications to leverage their advantages.
Emerging Technology-Based Services and Systems in Libraries, Educational Institutions, and Non-Profit Organizations
Book Chapter (Chapter 1)
Keywords: Academic Library Services, Artificial Intelligence, Ghana, Emerging Technologies